Development of novel nucleic acid therapy aimed at directly controlling liver fibrosis - Tomohiro Umezu; Masakatsu Takanashi; Koji Fujita; Akio Ishikawa; Yuichirou Harada; Yoshinari Matsumoto; Masahiko Kuroda; Yoshiki Murakami (Molecular Therapy: Nucleic Acids)
Currently, no drugs directly treat liver fibrosis. Previously, we have shown that treatment with miR-29a-3p improved liver fibrosis in a mouse model. To investigate the effectiveness of nucleic acid therapy at a lower dose, a modified nucleic acid was prepared based on miR-29a-3p. The original microRNA was changed to an RNA-DNA hybrid structure: the 2′ position of the RNA was modified with a fluorine base, and locked nucleic acid and phosphorothioate were crosslinked (hereafter called modified nucleic acid). In a mouse model of chronic liver disease treated with carbon tetrachloride (CCl4), the inhibitory effect on liver fibrosis was evaluated with oral administration of the modified nucleic acid. The modified nucleic acid was detected in the liver and gastrointestinal tract within 15 min of oral administration. After 5 weeks of stimulation with CCl4, oral administration of the modified nucleic acid for 2 weeks improved liver fibrosis; CCl4 stimulation was continued during this period as well. This treatment also suppressed the worsening of liver fibrosis. We developed a method to improve liver fibrosis orally using nuclease-resistant nucleic acids without using a drug delivery system. This method may be used as a new treatment for inhibiting the progression of liver fibrosis.